2017
DOI: 10.1097/ccm.0000000000002640
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Survey of the “Assessing Pain, Both Spontaneous Awakening and Breathing Trials, Choice of Drugs, Delirium Monitoring/Management, Early Exercise/Mobility, and Family Empowerment” (ABCDEF) Bundle

Abstract: Objective To assess the knowledge and use of the ABCDEF bundle to implement the Pain, Agitation, Delirium (PAD) guidelines. Design Worldwide On-line Survey. Setting Intensive care. Intervention A cross-sectional online survey using the Delphi method was administered to intensivists worldwide, to assess the knowledge and use of all aspects of the ABCDEF bundle (Assessment, prevention and management of pain; spontaneous awakening and Breathing trials; Choice of analgesia and sedation; Delirium assessment; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
151
1
41

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 208 publications
(205 citation statements)
references
References 40 publications
12
151
1
41
Order By: Relevance
“…ICU delirium is monitored only in 12% of ICUs; sedation > 24 h is predominantly induced with benzodiazepines which are also often used to treat delirium [4]. The study by Morandi et al [5] evaluating the same aspect of management worldwide has demonstrated that monitoring of delirium was implemented in 70% of ICUs while a proven diagnostic tool was used only in 42% of them.…”
mentioning
confidence: 99%
“…ICU delirium is monitored only in 12% of ICUs; sedation > 24 h is predominantly induced with benzodiazepines which are also often used to treat delirium [4]. The study by Morandi et al [5] evaluating the same aspect of management worldwide has demonstrated that monitoring of delirium was implemented in 70% of ICUs while a proven diagnostic tool was used only in 42% of them.…”
mentioning
confidence: 99%
“…For more than 40 years, intravenous antipsychotic medications have been used to treat delirium in hospitalized patients. 16,[35][36][37][38][39] In an international survey of 1521 intensivists, 65% reported that they treat delirium in the ICU with haloperidol and 53% reported that they treat delirium with atypical antipsychotic medications. 16 In this double-blind, randomized, placebo-controlled trial of intravenous antipsychotic medications for the treatment of delirium in the ICU, there was no evidence that either haloperidol or ziprasidone led to a shorter duration of delirium and coma.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperactive delirium can lead to unplanned removal of devices, 12 whereas hypoactive delirium prevents participation in nursing interventions, physical therapy, and occupational therapy. 13 Haloperidol, a typical antipsychotic medication, is often used to treat hyperactive delirium in the ICU, and surveys suggest that the drug is also used to treat hypoactive delirium [14][15][16][17] despite two small randomized trials that showed no evidence that haloperidol results in a shorter duration of delirium in the ICU than placebo. 18,19 Atypical antipsychotic medications, such as olanzapine, quetiapine, risperidone, and ziprasidone, are also used for this purpose, and one placebocontrolled trial has suggested a benefit, 20 whereas another 18 showed no evidence of benefit.…”
mentioning
confidence: 99%
“…Of note, neither antipsychotics nor dexmedetomidine have FDA approval for the treatment of delirium. In an international survey of 1521 intensivists, 65% reported that they treat delirium in the intensive care unit with haloperidol and 53% reported that they treat delirium with atypical antipsychotic medications [65], but there is no evidence-based literature showing efficacy of these medications for delirium treatment and symptom resolution. Despite current practice patterns, there are few data to support their definitive use in treating delirium.…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%